2019
DOI: 10.1126/scitranslmed.aau1749
|View full text |Cite
|
Sign up to set email alerts
|

Fluid assessment in dialysis patients by point-of-care magnetic relaxometry

Abstract: Magnetic resonance imaging (MRI) is a powerful diagnostic tool, but its use is restricted to the scanner suite. Here, we demonstrate that a bedside nuclear magnetic resonance (NMR) sensor can assess fluid status changes in individuals at a fraction of the time and cost compared to MRI. Our study recruited patients with end-stage renal disease (ESRD) who were regularly receiving hemodialysis treatments with intradialytic fluid removal as a model of volume overload and healthy controls as a model of euvolemia. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Our prior study in hemodialysis patients showed that excess fluid in hypervolemic patients can be observed by T2 relaxometry localized to skeletal muscle 44 . Of interest, changes in weight and blood chemistry indicated that two healthy control subjects experienced dehydration during this study.…”
Section: Physiology Of Dehydrationmentioning
confidence: 96%
See 2 more Smart Citations
“…Our prior study in hemodialysis patients showed that excess fluid in hypervolemic patients can be observed by T2 relaxometry localized to skeletal muscle 44 . Of interest, changes in weight and blood chemistry indicated that two healthy control subjects experienced dehydration during this study.…”
Section: Physiology Of Dehydrationmentioning
confidence: 96%
“…Lower extremity skeletal muscle offers an easily accessible site due to its relatively large size and a thin subcutaneous tissue layer for a portable MR sensor performing a localized measurement. A prior clinical study in hemodialysis patients from our group suggested that MRI localized to the skeletal muscle could identify fluid depletion . Hemodialysis patients are hypervolemic but 2 of the healthy control subjects became dehydrated based on their blood chemistry (serum osmolality and sodium) and weight change.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Fluid assessment in patients by point‐of‐care NMR relaxometry (schematic representation from Ref. [26]). Water loss (intracellular dehydration) is assessed using urinary tests 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, owing to the advancement of permanent-magnet design 2 , integrated electronics 3,4 , and antenna miniaturization 5 , portable NMR systems 6 have emerged as a viable surrogate. Thanks to the reductions in footprint, maintenance needs and price tag, the miniaturized sensor assemblies have extended their uses beyond conventional NMR laboratories to point-of-care medical diagnostics 7,8 , subterranean explorations 9 , flow metering 10 , fluid authentication 11 , and artefact preservation 12 . In those “field” applications, it is highly desirable that the machinery operates autonomously and self-optimizes based on properties of the samples under investigation.…”
Section: Introductionmentioning
confidence: 99%